2020
DOI: 10.1111/anu.13039
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spray‐dried porcine plasma on gilthead seabream (Sparus aurata) intestinal microbiota

Abstract: The effect of spray‐dried porcine plasma (SDPP) on the intestinal histological organization and autochthonous microbiota composition was evaluated in Sparus aurata. Fish were fed a basal diet (51 g/kg protein, 17 g/kg fat, 20.6 MJ/kg gross energy) and a diet containing 3 g/kg SDPP for 95 days (initial body weight, BW = 9.5 ± 0.2g, mean ± SD). The inclusion of SDPP promoted growth (p < .05), being fish fed the SDPP diet 6.2% (BW = 88.2 ± 1.6 g) heavier than the control (BW = 82.7 ± 3.2 g). SDPP increased the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 64 publications
5
12
0
Order By: Relevance
“…In addition, we also evidenced that dietary SDPP promoted skin development by increasing the thickness of the epidermis and the stratum spongiosum of the dermis, providing new evidence of the dietary supplement at mucosal level. Similarly to the antecedent obtained from intestinal mucosa ( 53 ), our study showed that dietary SDPP increased the density of mucous cells in the epidermis. The above-mentioned results on growth, diet utilizationand mucosal tissue development might be attributed to the nutritional profile of SDPP that includes growth factors, immunoglobulins and bioactive peptides ( 27 , 54 , 55 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, we also evidenced that dietary SDPP promoted skin development by increasing the thickness of the epidermis and the stratum spongiosum of the dermis, providing new evidence of the dietary supplement at mucosal level. Similarly to the antecedent obtained from intestinal mucosa ( 53 ), our study showed that dietary SDPP increased the density of mucous cells in the epidermis. The above-mentioned results on growth, diet utilizationand mucosal tissue development might be attributed to the nutritional profile of SDPP that includes growth factors, immunoglobulins and bioactive peptides ( 27 , 54 , 55 ).…”
Section: Discussionsupporting
confidence: 84%
“…It is well known that inclusion levels of 4–8% are recommended for optimal results in higher vertebrates like pigs ( 25 ), poultry ( 24 , 26 ), cats ( 51 ) and rats ( 52 ). Recently, it was also assayed its beneficial effects on several freshwater and marine fish species of importance due to their economic value such as rainbow trout ( 30 ), Nile tilapia ( 32 ) and gilthead sea bream ( 31 , 53 ). Under the present experimental conditions, our results were in agreement with the available literature on different teleost species, confirming the beneficial effects of dietary SDPP inclusion on somatic growth performance and feed efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, variation between individual fish can be represented as a whole since pooled intestinal content samples were obtained from individuals fed with the same diet. This practice was carried out in order to avoid bias, as has been proposed in previous studies [ 47 , 48 , 49 ] Total DNA from each pool was obtained as described by Martínez et al (1998) [ 50 ]. The dried DNA pellet was resuspended in 100 μL of DECP water (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Out of this, the vast majority was used for rendering, land filling, pet food and, in a minor percentage, for food [110]. Mostly due to restrictions imposed by legislation, the valorisation of meat co-products in animal feed is quite limited with the remarkable exception of plasma from pork blood, which is used for broilers, piglets and dairy cows feeding and, more recently, for aquaculture purposes [111,112]. However, the red cells fraction is still not exploited for these purposes.…”
Section: At Processing and Manufacturing Levelmentioning
confidence: 99%